2000
DOI: 10.1159/000027137
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose versus Low-Dose Cisplatin Chemotherapy plus Treosulfan in Epithelial Ovarian Carcinoma FIGO II–IV: Results of a Prospective Randomized Trial

Abstract: Background: Combination chemotherapies of platinum compounds with alkylating agents have been the standard treatment for patients with advanced ovarian carcinoma over the last decades. The recent development of taxans has added a group of new promising agents; however, long-term results are not yet available. Platin derivates have proven to be an indispensable part in combination chemotherapies for ovarian carcinoma. The dose intensity of cisplatin is, however, still a matter of debate. We report on the long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Treosulfan (L-treitol 1,4-bismethanesulfonate, Ovastat s ) is a water-soluble prodrug of a bifunctional alkylating cytostatic and has mainly been used in the therapy of advanced ovarian cancer. [10][11][12][13] Treosulfan caused only moderate side effects in patients, but these were manageable and rapidly reversible. 13,14 Recently, we have shown that Treosulfan can be used to induce donor-specific tolerance over complete MHC barriers using either T-cell-depleted BMC or hematopoietic stem cells.…”
mentioning
confidence: 99%
“…Treosulfan (L-treitol 1,4-bismethanesulfonate, Ovastat s ) is a water-soluble prodrug of a bifunctional alkylating cytostatic and has mainly been used in the therapy of advanced ovarian cancer. [10][11][12][13] Treosulfan caused only moderate side effects in patients, but these were manageable and rapidly reversible. 13,14 Recently, we have shown that Treosulfan can be used to induce donor-specific tolerance over complete MHC barriers using either T-cell-depleted BMC or hematopoietic stem cells.…”
mentioning
confidence: 99%